Per- and polyfluoroalkyl substances (PFAS) in consumer products: Current knowledge and research gaps - Dewapriya, Pradeep; Chadwick, Lachlan; Gorji, Sara Ghorbani; Schulze, Bastian; Valsecchi, Sara; Samanipour, Saer; Thomas, Kevin V.; Kaserzon, Sarit L. (Journal of hazardous materials letters, 2023)
While several sources of per- and polyfluoroalkyl substances (PFAS) are known, their use in consumer household products is far less explored. The aim of this study was to provide comprehensive bottom-up analysis of the types and concentrations of PFAS reported in the literature over the past decade. A total of 52 studies revealed 107 PFAS belonging to 15 different categories in 1040 consumer products. The highest number of products tested were from the USA (n = 389) followed by the Czech Republic (n = 111). Mean PFAS concentrations were highest in household firefighting products, followed by textile finishing agents and household chemicals. The highest diversity of PFAS was reported in textiles (72 PFAS). Fluorotelomer alcohol (FTOH), polyfluoroalkyl phosphate esters (PAPs), perfluorocarboxylic acid (PFCA) and perfluorosulfonic acid (PFSA) are the classes of PFAS of high interest. Eight out of 52 studies used High-Resolution Mass Spectrometry techniques. Highlighted knowledge gaps included (i) the development of analytical methods for detecting a range of PFAS in consumer products, (ii) method validation and QA/QC approaches, (iii) application of suspect and non-target analysis, and (iv) an understanding of human exposure risk. This review highlights that the presence of PFAS in consumer products is of concern and remains underexplored. [Display omitted] •Comprehensive analysis of PFAS present in household consumer products.•107 PFAS found in 15 consumer product categories.•A wide range of PFAS at concentrations between 2.6 × 10-7 and 29,000 ppm have been detected.•Textiles > household chemicals > and cosmetics show the highest average concentrations among personal use items investigated.•The presence of PFAS in consumer products is of concern and requires stronger regulation.